Effect of Alcohol Prevention Program on Subject Well-being Scale, Alcohol Abstinence Self-Efficacy Scale and Alcohol Decisional Balance Scale of Alcohol Related Prisoners in Correctional Institutions in Korea - Jung, Hyun-Ok; Han, Seung-Woo (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: This research intends to determine the intervening effect of alcohol prevention education programs on subjective well-being, alcohol abstinence self-efficacy, and alcohol decisional balance of alcohol-related prisoners. Methods: The subjects of the research were 25 alcohol-related prisoners who were detained in S district prisons in South Korea. The program was organized into less than 10 subjects for each session and carried out in three rounds from June 1 to July 2, 2019. A total of eight sessions programs were provided for four weeks, two times a week for each session. The collected data were analyzed with frequency, percentage, and paired t-test using the SPSS/WIN 21.0 program. Results: After the alcohol prevention training program, there was significant difference in subjective well-being scores (t=3.05, p= .005) and alcohol decisional balance score (t=2.16, p=.041). However, there was no significant difference in the abstinence self-efficacy score (t=-1.17, p=.254). Conclusion: Implementing the program will not only enriches the quality of life of alcohol-related prisoners by improving inherent positive emotions but also contribute to re-socialization and reduction of recidivism by making them aware of shortcomings rather than the benefits of alcohol.